Analisis Kinerja Keuangan Perusahaan Rokok yang Tercatat di Bursa Efek Indonesia Periode 2020-2023 - Zafar, Andriana Okta; Rifa’i, Muhamad; Gunawan, Cakti Indra (Journal of Indonesian Economic Research, 2025)
The aim of this research is to determine the financial performance of cigarette companies listed on the Indonesia Stock Exchange for the 2020-2023 period based on liquidity, solvency and profitability analysis. Type of quantitative research. The population uses 4 cigarette companies registered on the IDX (PT Gudang Garam Tbk, PT Hanjaya Mandala Sampoerna Tbk, PT Indonesia Tobacco Tbk, and PT Wismilak Inti Makmur Tbk). The research uses primary data in the form of financial reports for the 2020-2023 period. The results of financial performance analysis based on financial ratio analysis, show that publicly traded cigarette companies listed on the IDX generally face challenges in liquidity, solvency and profitability, with most companies showing ratios below industry standards, although there are some that show good debt management and performance improvements. Based on the results of this analysis, it is recommended that company management focus on optimizing current asset management to increase liquidity, reduce dependence on debt by increasing equity, and increase operational efficiency to reduce costs and increase profit margins.